Lumbosacral Plexopathy After Carbon-ion Radiation Therapy for Postoperative Pelvic Recurrence of Rectal Cancer: Subanalysis of a Prospective Observational Study (GUNMA 0801) - Takuya Kumazawa, MD, PhD; Shintaro Shiba, MD, PhD; Yuhei Miyasaka, MD, PhD; Masahiko Okamoto, MD, PhD; Daijiro Kobayashi, MD, PhD; Tatsuya Ohno, MD, PhD (Advances in Radiation Oncology)
Purpose: Data are lacking on the risk factors for radiation-induced lumbosacral plexopathy (RILSP) after carbon-ion radiation therapy (CIRT) for pelvic tumors, such as postoperative recurrence of rectal cancer. We investigated the incidence of RILSP and the associated dosimetric parameters using data from a prospective study of CIRT for postoperative pelvic recurrence of rectal cancer (GUNMA 0801). Methods and Materials: The GUNMA 0801 study included 28 patients, of which we analyzed 20 without lumbosacral plexopathy prior to CIRT. The total dose of CIRT was 73.6 Gy (relative biological effectiveness [RBE]) in 16 fractions. The incidence of RILSP and parameters of the dose-volume histogram were evaluated for the lumbosacral plexuses. RILSP was graded according to the Common Terminology Criteria for Adverse Events version 4.0. Results: Median follow-up was 24 months. The incidence of all RILSP (grades 1 and 2) and grade 2 RILSP was 22.5% (9/40) and 10% (4/40) of 40 lumbosacral plexuses in 20 patients, respectively, and no grade ≥ 3 toxicity was observed. Throughout the dose range, the volumes of the irradiated lumbosacral plexuses were significantly higher in patients with RILSP than in patients without RILSP (P < .001 for Dmax, D0.5 cm3 − D2 cm3, V20 Gy(RBE) − V70 Gy(RBE)). D2 cm3 and V50 Gy(RBE) were considered useful for receiver operating characteristic analysis. Cutoff values for RILSP were 73.82 Gy(RBE) and 33.2% for D2 cm3 and V50 Gy(RBE), respectively. Conclusions: We demonstrated the incidence and predictive dosimetric parameters for RILSP after CIRT and showed that D2 cm3 ≥ 73.82 Gy(RBE) and V50 Gy(RBE) = 33.2% are cutoff values for predicting RILSP. These results would improve treatment plans using CIRT for patients with pelvic recurrences of rectal cancer.